Antibacterial effects of curcuma (Curcuma xanthorriza) on Vibrio alginolyticus in baramundi - Eva Ayuzar; Rachmawati Rusydi; Muliani Muliani; Angelia Angelia; Dira Fajria (Arwana: Jurnal Ilmiah Program Studi Perairan, 2023)
This study aimed to determine the inhibitory power of the growth of Vibrio alginolyticus bacteria, phytochemicals, and the effectiveness of Curcuma rhizome extract against the prevention of Vibrio alginolyticus infection in white snapper. The research was conducted in January - July 2022 at Malikussaleh University. The research method consists of the preparation of curcuma extract, preparation of Vibrio alginolyticus bacteria, inhibition zone test, preparation of test biota, application of Curcuma extract through immersion in fish, challenge test of Vibrio alginolyticus, and fish rearing. The research design used was a Complete Randomized Design (RAL)-Non-Factorial. The study consisted of 2 stages, namely (1) antibacterial test of rhizome extract against Vibrio alginolyticus, with the treatment of aromatic ginger, Curcuma, zingiber rhizome extracts at doses of A (60%), B (80%), and C (100%), respectively.  The results showed that Curcuma rhizome extract is the best. The results of phytochemical tests showed that the Curcuma rhizome plant was positive for flavonoids, tannins, alkaloids, saponins, terpenoids, and phenolics, but negative for steroid compounds. So continued the Phase 2 study with the aim of testing the effectiveness of temulawak rhizome extract at doses: A (70%), B (80%), C (90%), and D (100%). The results of the phase 2 study showed that the most effective concentration in inhibiting the growth of Vibrio alginolyticus bacteria is temulawak rhizomes with a concentration of 100%. Rated survival rate 86.67%), duration of healing (24 hours 28 minutes), and percentage of recovery from white snapper (86.7%).